Living With Earthquake and Flood Hazards in Jammu and Kashmir, NW Himalaya - Shah, Afroz Ahmad; Khwaja, Sheeba; Shah, Bilal A.; Reduan, Qibah; Jawi, Zirah (Frontiers in Earth Science, 2018)
Jammu and Kashmir is one of the most politically challenged regions in NW Himalaya, and perhaps also one of the most unfortunate portions of the planet Earth where political and natural disasters have greatly devastated the progressive development of the region. The geological past of this region suggests that it was formed when Indian tectonic plate collided with the Eurasian plate, and this also developed some intermontane basins, which house most of the population of the region. As the tectonics is still actively shaping the topography, geology, geomorphology, and climate of the region, the occurrence of earthquakes and floods in the area is potentially unavoidable. Our knowledge about the causes of earthquakes tells us that it is time to put more emphasis on preparedness rather than on the prediction, which is partly true of flood hazards as well. This paper aims to highlight the urgent need to educate local students and community leaders about the science of earthquakes, and floods, and how to live with such hazards in Jammu and Kashmir. This is backed by the field evidence where interactions will locals suggest an urgent need of comprehensive planning to educate, engage, and train local students about the science of earthquake and flood hazards. The entire population of Jammu and Kashmir is >12 million, and the vulnerability to hazards is unavoidable unless a robust framework is planned for the region. Our fieldwork shows that Kashmir conflict has a negative impact on the mindset of people because they take earthquake and flood hazards as of secondary importance than the resolution of the political issue. Therefore, we conclude that scientific work related to hazards is required to educate local people by organising a series of workshops, training sessions, course modules, international conferences, public talks, together with the dissemination of awareness about adopting earthquake resistant construction model. However, such efforts will only be effective on the ground if the political problem is resolved. Hence India and Pakistan must sit on the table and address the Kashmir problem for the safety and security of everyone in the region.